Enhancing student motivation and learning engagement in physics through science olympics - Fredyrose Ivan L. Pinar; Lydia S. Roleda; Sotero O. Malayao Jr. (Journal of Education and Learning (EduLearn), 2026)
Science olympics is a comprehensive educational initiative designed to foster active student engagement and motivation within a school-wide framework. This study explored the impact of science olympics on students’ motivation and learning experiences in physics contexts. Rooted in design thinking and problem-based learning, the science olympics program encourages collaborative and competitive activities, aligning with Kolb’s experiential learning theory. A total of 220 participants from grades 7-12 were divided into competing teams within 4 different houses, employing a multilevel categorization approach within each house. Utilizing an embedded mixed-method research design, this study collected quantitative data through surveys and post-event evaluations, then qualitative data were derived from student perceptions, interviews, and teacher feedback. The results demonstrated a significant increase in student learning engagement in physics, across all grade levels. Moreover, science olympics emerged as a potent avenue for developing 21st-century skills and reinforcing acquired knowledge, both inside and outside the classroom. This innovative approach positively influenced students’ conceptual understanding of physics and enhanced their motivation to learn, showcasing the potential of such dynamic and interdisciplinary educational initiative.